Pelatihan Implementasi Teknologi Informasi Untuk Menangkap Peluang Usaha Bagi Generasi Muda Di Kecamatan Gadingrejo - Putra, Nanda Pramana (Jurnal Pemberdayaan Ekonomi, 2025)
Purpose: This community service program aims to equip young people in Gadingrejo Subdistrict with knowledge and skills in using information technology (IT) to identify and utilize business opportunities through e-commerce and digital platforms. Research methodology: The program was conducted through a combination of presentations and hands-on training using projectors and IT tools. Participants received material on IT concepts, including the use of digital applications to support entrepreneurship. After the presentation, they practiced using relevant applications and engaged in interactive discussions. Results: The training was attended by 53 participants who showed high enthusiasm and active involvement throughout the session. They demonstrated improved understanding of how IT can enhance business potential and efficiency. Many participants asked questions and directly applied what they learned during the session. Conclusions: The program effectively introduced IT-based business practices to youth, fostering interest and capacity in digital entrepreneurship. The interactive method enhanced learning outcomes and participant satisfaction. Limitations: The program was limited to one session and a small group of participants. Broader implementation and long-term evaluation are needed to assess its wider impact. Contribution: This initiative contributes to youth empowerment and digital transformation in the MSME sector. It highlights the role of IT education in building competitive local entrepreneurs capable of navigating the digital economy.